Discrimination and the effects of drug testing on black employment - Abigail Wozniak (W.E. Upjohn Institute for Employment Research, 2013)
Nearly half of U.S. employers test job applicants and workers for drugs. I use variation in the timing and nature of drug testing regulation to study discrimination against blacks related to perceived drug use. Black employment in the testing sector is suppressed in the absence of testing, consistent with ex ante discrimination on the basis of drug use perceptions. Adoption of pro-testing legislation increases black employment in the testing sector by 7-30 percent and relative wages by 1.4-13.0 percent, with the largest shifts among low skilled black men. Results suggest that employers substitute white women for blacks in the absence of testing.
Keywords: J7; J15; K2; K3; M5; 330; Employment drug testing; discrimination; employment; Current Population Survey